Probability based Watershed Segmentation Algorithm for Multiple Brain Tumor Detection - Busa, Srikanth; Reddy, E.S (International Journal of Computer Sciences and Engineering, 2018)
Automatic tumor detection is one of the difficult tasks in medical image diagnosis due to variations in size, type, shape and location of tumors. In the traditional brain tumor detection models, intra and inter slice resolutions may affect the segmentation accuracy. In addition, brain tumors have different intensities overlapping with normal tissue. In this paper, we have proposed an automatic tumor detection framework to detect the multiple tumors in brain tumor databases. This system has three main phases, namely image preprocessing, iterative threshold image enhancement and multi tumor segmentation algorithm. Experimental results show that our proposed system efficiently detects multiple tumors at different locations in the brain tumor image dataset.